The Influence of Health Promotion Through Educational Game Media on Knowledge of the Impact of Gadget Use on Elementary School Students 010056 Sei Renggas, Kisaran City in 2024 - Siregar, Dian Maya Sari; Kartika, Dwi Yoga; Rosdiana, Rosdiana (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
The use of gadgets among children is increasingly causing concern and can have a negative impact on their development. In 2022, around 33.44% of early childhood in Indonesia have used gadgets, the majority of children over 5 years old have accessed the internet with a percentage of 88.99%.In the initial survey, it was found that students' knowledge was still lacking regarding the importance of maintaining a balance in time when using gadgets.To determine the effect of health promotion through educational game media on knowledge about the impact of gadget use on students of SDN 010056 Sei Renggas. Using One Group Pretest Posttest design. The sample was all 5th and 6th grade students totaling 37 students. Data analysis using univariate, normality test with Shapiro Wilk Test and difference test using Wilcoxon Rank Test. The mean increase in respondents' knowledge was 5.57, withPositive Ranksof 37, Mean Rank of 19.00, while Sum of Ranks of 703.00. In addition, a significance value of 0.000 <0.05 was obtained, which indicates that there is a significant difference between the pretest and posttest results. There is an influence of health promotion through educational games of snakes and ladders in increasing knowledge about the impact of gadgets on students of UPTD SDN 010056 Sei Renggas. It is hoped that the school can provide counseling on the impact of gadget use using educational game media, which can attract students' attention so that the message or information to be conveyed can be easily received and can be applied in everyday life.